Challenges for barley production in India - S Verma, R P; Sarkar, B; Kharub, A S; Selvakumar, R (Indian Farming, 2015)
Barley cultivation in India was facing stiff challenges in terms of area with wheat in winter season, as the crop was considered less remunerative due to less MSP and market price, resulting drastic reduction in area and production. Recent changes in situation triggered by the industrial demand in malting and brewing has given it a new lease of life and it is becoming commercial crop. Contract farming on larger scale has started in Punjab, Haryana and Rajasthan. The new challenges for production and protection technologies in addition to the genetic improvement are being envisaged because of its shift to optimally managed conditions. We may also have to look for lodging resistance through new plant type in addition to the requirements of genetic resistance to biotic and abiotic stresses and better grain quality. The changing climate and shortage of water are general problems of crop production and barley cultivation can be a good option to mitigate with such challenges.